The Relationship Between Protein Intake And The Incidence Of Chronic Lack Of Energy (KEK) In Pregnant Women - Inatul Hidayah; Fitriani; Asnidar (Jurnal Life Birth, 2021)
According to WHO additional protein for pregnant women is 0.75 grams/kg of body weight. And overall the amount of protein that will be needed by pregnant women is approximately 60-70 grams every day or about 925 grams of the total protein needed during pregnancy. The purpose of this research is to find out the relationship between protein intake and the incidence of chronic energy deficiency (KEK) in pregnant women in Puskesmas Ponre Bulukumba Regency. This type of research is quantitative research where this study uses a research design with a cross-sectional study design. This cross-sectional design is a research design by taking measurements or observations at the same time-dependent variables and independent variables at a given moment. The result of this study is that there is a relationship between protein intake and chronic energy deficiency (KEK) in pregnant women. Conclusions and advice For health centers and health workers need to provide ongoing education and assistance about KEK in pregnant women and fulfillment of nutrition during pregnancy to reduce the prevalence of KEK in the working area of puskesmas ponre.